“My Story Bursts Forth…”: Re-visioning Female Subjecthood in Gendered Folktales in Northern Ghana - Yitah, H. (Fabula, 2018)
This paper examines contemporary retellings of Ghanaian (Kasem) folktales that engage critically with the social roles and cultural values in the tra-ditional corpus. While in traditional folktales supernatural forces are unleashed to punish females who pursue their own strivings, thus regulating gender iden-tity, in the retold tales female protagonists deploy nantandia, a local Kasem term which encompasses intelligence, initiative and courage, to thwart the power of the supernatural and assert their own subjecthood.